KARAKTERISTIK PENDIDIKAN TASAWWUF MENURUT LOUIS MASIGNON - Soheh, Moh (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2018)
Rasulullah did the Uzlah to the cave of Hira 'is the first revelation in the form of "Iqra", the first word of revelation revealed by Allah SWT, through the angel Gabriel, with the aim that the Messenger of Allah can read and by reading produce knowledge, which is passed through contemplation by standing, lie down, and sit glorifying the greatness of Allah SWT. The benefits of knowledge in the form of qur'aniyah and kauniyah can give benefit to the people of the world.